Automating exploratory spatial data analysis (ESDA) for vector and raster data : development and evaluation of the autoESDA Python library - Rautenbach, Victoria-Justine (University of Pretoria, 2024)
Dissertation (MSc (Geoinformatics))--University of Pretoria, 2023.